2012
DOI: 10.1021/bc3001003
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Transfection of Hepatocytes Mediated by mRNA Complexed to Galactosylated Cyclodextrins

Abstract: In this study, we aimed at specific targeting of polycationic amphiphilic cyclodextrins (paCDs) to HepG2 cells via the asialoglycoprotein receptor (ASGPr). The transfection efficiencies of paCDs modified with galactose moieties were evaluated. In preliminary experiments, attempts to transfect HepG2 cells with pDNA complexed with different modified paCDs resulted in very low transfection levels. In additional series of experiments, we found out that nucleic acid/cyclodextrin complexes (CDplexes) were efficientl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 58 publications
1
32
0
Order By: Relevance
“…Rejman, García Fernández and co-workers explored this approach for the preparation of bGal-coated pGaCDs (111) intended for hepatocyte-specific nucleic acid delivery. 168 Since replacement of cationic centres by sugar motifs in paCDs was detrimental for CDplex stability, grouping the recognition elements into multivalent glycodendrons prior to paCD conjugation was judged convenient. The coating moiety consisted of a trivalent b-Dgalactopyranosyl antenna, built on a pentaerythritol scaffold, armed with an isothiocyanate group (110) for thiourea-forming conjugation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Rejman, García Fernández and co-workers explored this approach for the preparation of bGal-coated pGaCDs (111) intended for hepatocyte-specific nucleic acid delivery. 168 Since replacement of cationic centres by sugar motifs in paCDs was detrimental for CDplex stability, grouping the recognition elements into multivalent glycodendrons prior to paCD conjugation was judged convenient. The coating moiety consisted of a trivalent b-Dgalactopyranosyl antenna, built on a pentaerythritol scaffold, armed with an isothiocyanate group (110) for thiourea-forming conjugation.…”
mentioning
confidence: 99%
“…The fact that high transfection levels were achieved with mRNA, which is translated in the cytoplasm, much higher as compared with mRNA complexes formulated with the reference compound JetPEIt-Hepatocyte, supported this assumption. 168 …”
mentioning
confidence: 99%
“…In another study PCI failed to enhance the transfection rate of HepG2 cells transfected with polycationic amphiphilic cyclodextrin-DNA complexes but did enhance the transfection of the cells with complexed mRNA. The authors concluded that the low transfection rate for DNA was caused by problems with the complexed DNA entering the nucleus and may not be indicative that PCI per se failed to increase the delivery of complexed DNA to the cytosol [118]. An approach with low density lipoproteins as carriers for siRNA demonstrated only a moderate increase of transfection by PCI (38% gene knock-down without PCI versus 78% gene knock-down with PCI) [119].…”
Section: Physicochemical Techniquesmentioning
confidence: 99%
“…Bioreducible lipoplexes were thus added to SYBR Green I in DMEM either supplemented or not with 10% FBS. The changes in fluorescence, indicating an increase in the amount of free DNA that is the only accessible for the probe, were measured with a fluorometer [40]. Lipoplexes should remain intact upon dilution in cell culture media.…”
Section: Dna Release From Bioreducible Lipoplexes: the Yin Effect Of mentioning
confidence: 99%